Time perspective, sports club membership, and physical self-concept among adolescents: a person-centered approach - Konowalczyk, Svenja; Rade, Clemens; Mello, Zena (Journal of adolescence, 2019)
Introduction - Time perspective is defined as thoughts and feelings about the past, present, and future and is theorized to underlie human behavior. Prior research has shown relationships among time perspective and academic achievement, substance use, and risky-driving. In this study, time perspective was extended to sports club membership and physical self-concept among adolescents. - Methods - Time perspective was assessed with a scale that measures positive and negative feelings about the past, present, and future. Latent time attitude profiles were generated with data that included sports club membership and physical self-concept. Participants were German (N=901; 46.2% female), Luxembourgian (N=661; 46.7% female), and Spanish (N=789; 49.0% female) adolescents (12–18 years-old). - Results - Latent profile analyses indicated that across the three samples the same number and type of profiles were observed: Ambivalent, Balanced, Optimistic, Past Negative, and Positive. Time attitude profiles were related to sports club membership and physical self-concept. Adolescents with positive attitudinal profiles were more engaged in sports clubs and reported a higher physical self-concept than adolescents in negative attitudinal profiles. - Conclusions - Time perspective was conceptualized as time attitudes and operationalized as positive and negative feelings about the past, present, and future. Results showed that five latent time attitudes profiles were observed and that profile membership was associated with sports club membership and physical self-concept. These associations were demonstrated with three independent samples. Findings were discussed in light of implications for intervention programs that use time perspective to promote physical health among adolescents.
Gesehen am 20.05.2019